[18F]-FDG PET-CT in Malignant Melanoma - Teodora Sidonia Mititelu; Mihaela Raluca Mititelu; Sandica Bucurica; Daniel Octavian Costache (Diagnostics)
Background/Objectives: Malignant melanoma (MM) is an aggressive neoplasm with a rising global incidence. Accurate staging and risk stratification are essential for guiding therapeutic decisions and improving patient prognosis. [18F]-FDG PET-CT enables the non-invasive assessment of tumor metabolic activity, offering a valuable adjunct to histopathological evaluation. However, the correlation between PET-CT findings and established prognostic markers in MM, such as Breslow thickness, ulceration, and mitotic rate, remains insufficiently explored. Methods: This retrospective observational study included 61 patients diagnosed with MM, of whom 48 met the inclusion criteria. Quantitative and qualitative variables such as SULmax, Breslow thickness, Ki-67 expression, and mitotic rate were analyzed using descriptive statistics, while correlations between PET-CT findings, SLNB, and histopathological characteristics were assessed using Spearman’s correlation test. A p-value < 0.05 was considered statistically significant. Results: Significant associations were identified between ulceration and both overall metastases (p = 0.01) and pulmonary metastases (p = 0.02). Breslow thickness showed a positive correlation with metastatic spread (p = 0.01), reinforcing its role as a key prognostic indicator. Perineural and vascular invasion were significantly associated with intra-abdominal metastases (p < 0.001 and p = 0.0007, respectively). Tumor-infiltrating lymphocytes (TILs) were inversely correlated with intra-abdominal metastases (p = 0.05), while sentinel lymph node positivity correlated with the presence of regional (p = 0.008) and distant (p = 0.02) metastases. Additionally, subcutaneous SULmax values were significantly higher in male patients compared to females (p = 0.04). Conclusions: Integrating PET-CT metabolic parameters with histopathological markers enhances the assessment of MM aggressiveness and metastatic potential. By refining risk stratification, PET-CT may contribute to personalized therapeutic strategies and improved patient management in MM.